Formulasi Sediaan Obat Kumur (Gargarisma) Kombinasi Ekstrak Daun Jambu Biji dan Biji Pinang - Gebbrina, Frank Sisca; Putra, Fajrian Aulia; Syafputri, Try Maya (Jurnal Medisains Kesehatan, 2025)
Mouthwash is a liquid dosage form used to prevent and treat oral health problems. However, many commercial mouthwashes contain alcohol, which may cause side effects in certain individuals. This study aimed to formulate and evaluate a mouthwash (gargle) preparation made from a combination of guava leaf extract (Psidium guajava L.) and areca nut seed extract (Areca catechu L.). The extracts were obtained by maceration using 70% ethanol. Three formulations were prepared: F1 containing 3% guava leaf extract and 2.5% areca nut extract, F2 containing 3.5% guava leaf extract and 2.5% areca nut extract, and F3 containing 4% guava leaf extract and 2.5% areca nut extract. Physical evaluations included organoleptic tests, pH, viscosity, clarity, homogeneity, and hedonic (preference) tests. Results showed that all formulations met the required physical quality standards. Based on the preference test, formulation F3 received the highest score (26.2), surpassing F1 and F2. The combination of guava leaf and areca nut extracts shows potential as a natural, effective, safe, and alcohol-free mouthwash formulation.